Mass media campaigns to reduce unnecessary caesarean sections: a systematic review - Ana Pilar Betran; Maria Regina Torloni; Vanessa Brizuela (BMJ Global Health, 2020)
Introduction The worldwide increase in unnecessary caesarean sections (CSs) is a major global health issue. Mass media campaigns have been used in several countries to reduce this trend. The objectives of this systematic review were to identify, critically appraise and synthesise the findings, including the barriers and enablers, of mass media campaigns directed at lay people to reduce unnecessary CS.Methods We included any study design that reported health communication mass media campaigns directed at lay people with the specific objective of reducing unnecessary CS, created by any agent, in any format. We searched seven electronic databases without language restrictions, from inception to February 2019. Experts in the field were contacted.Results The search yielded 14 320 citations; 50 were selected for full-text reading; and one was included. Six other reports were included. The seven campaigns were conducted in 2009–2017, mostly in Latin America. Most campaigns were independent efforts by non-governmental or activist organisations. Only one campaign conducted formative research and pretested the intervention. All campaigns used indirect communication, mostly through internet channels; two campaigns also used direct communication with the public. None assessed their effects on CS rates. Only two campaigns measured their impacts on participants’ knowledge, attitudes and birth preferences but only in the short term. The main barriers were lack of financial and human resources. The main enablers were the enthusiasm of volunteers, the participation of famous persons/celebrities and the involvement of communication professionals.Conclusions There are few mass media campaigns directed at lay people to reduce CS. Most campaigns did not use key principles recommended for the creation and implementation of health communication interventions, and none assessed their effects in reducing CS rates. If media campaigns can play a role in modifying population views towards CS, there is a need for more rigorous studies including impact assessment.PROSPERO registration number CRD42019120314.